Human Systems Integration to Enhance Maritime Domain Awareness for Port/Harbour Security - Shahbazian, Elisa (IOS Press, 2013)
The multidisciplinary Advanced Research Workshop (ARW) entitled “Human Systems Integration to Enhance Maritime Domain Awareness for Port/Harbour Security” brought together experts in the domains of Harbour/Port Security and Human Factors, as well as Knowledge Management, Knowledge Exploitation and Decision Support Technologies from the NATO, NATO Partner and Mediterranean Dialogue Countries, who presented and discussed various aspects of the problems of enhancing Maritime Domain Awareness in Harbours/Ports through application of Human-System Integration and advanced technologies. Presentations by domain, human factors and technology experts were devoted to enhance understanding of the problems, approaches, methodology and technical language used in various disciplines related to designing harbour security systems and integration of human factors in such systems. This volume comprises contributions by these lecturers and investigative reports by the working groups on the process, organizations and technology requirements to meet challenges of the seaport infrastructure security. Topics include: Effective representation of domain characteristics and user requirements; Modelling of human systems, their behaviour and their impact on port security; Information modelling, characterization and processing for situation awareness and decision support; Designing the situation and threat assessment systems; Methodology for a human/machine information system to support harbour security; Regulations, infrastructure, stakeholder responsibilities, as well as technology requirements to meet challenges of cargo security.